The Justice Gap and the Promise of Criminological Research. Russian Journal of Economics and Law - R. A. Leo (Russian Journal of Economics and Law)
Objective: to summarize and study the law-application errors during preliminary interrogation, court investigation, and conviction in the American criminal justice system.Methods: dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors, which predetermined the following research methods: formal-logical and sociological.Results: the work describes in detail and considers four main causes of law-application errors occurring during preliminary interrogation, court investigation, and conviction in the American criminal justice system. These include: false confessions, eyewitness misidentification, forensic error, and perjured jailhouse informant testimony. Hence, it is not accidental that the main task of empirical research of criminologists and other researchers in the past two decades has been a call for greater transparency in the evidence-gathering process and the development and implementation of best practices based on social science research. Developing conceptual knowledge is important not only for creating a more systematic, generalizable and respectable criminology of wrongful conviction, but also to better inform policy-makers’ understandings that people’s lives may be at stake, as well as trade-offs of wrongful convictions.Scientific novelty: the work considers the current problems in the American criminal justice system, that occur during preliminary interrogation, court investigation, and conviction. Among them are the problems of police interrogations, false confessions and court errors, leading to wrongful convictions.Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering the issues related to the minimization of errors occurring at the stages of preliminary interrogation, court investigation, and conviction in the American criminal justice system.The article was first published in English language by Criminology, Criminal Justice, Law & Society and The Western Society of Criminology Hosting by Scholastica. For more information please contact: CCJLS@WesternCriminology.org. For original publication: Leo, R. A. (2014). The Justice Gap and the Promise of Criminological Research, Criminology, Criminal Justice, Law & Society, 15 (3), 1–37. Publication URL: https://ccjls.scholasticahq.com/article/419-the-justice-gap-and-the-promise-of-criminological-research